1980
DOI: 10.1037/0021-843x.89.6.728
|View full text |Cite
|
Sign up to set email alerts
|

Impaired recognition of self-expressed thought in patients with auditory hallucinations.

Abstract: This study tested the hypothesis that psychiatric patients with a history of auditory hallucinations would show impaired recognition of their own thoughts relative to nonhallucinating patients. The reasoning underlying this proposal was that given the need to discriminate between one's own lexical thought and a voice from another source, the person less familiar with the properties of his or her thinking would more likely mislabel the source. Twelve hallucinators and eight nonhallucinators were asked to identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0
2

Year Published

1992
1992
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(31 citation statements)
references
References 14 publications
2
27
0
2
Order By: Relevance
“…There are diverse theoretical positions in relation to hallucinations, but all maintain that such experiences are actually private events attributed to an external source (Bentall, 1990;Bentall, Haddock, & Slade, 1994;Frith, 1995;Helbrun, 1980;Morrison, Haddock, & Tarrier, 1995). Based on this assumption, Bentall (1990) has stressed the importance of skill in judging the source of a perceived event for understanding hallucinatory phenomena, which is been called "reality discrimination".…”
mentioning
confidence: 95%
“…There are diverse theoretical positions in relation to hallucinations, but all maintain that such experiences are actually private events attributed to an external source (Bentall, 1990;Bentall, Haddock, & Slade, 1994;Frith, 1995;Helbrun, 1980;Morrison, Haddock, & Tarrier, 1995). Based on this assumption, Bentall (1990) has stressed the importance of skill in judging the source of a perceived event for understanding hallucinatory phenomena, which is been called "reality discrimination".…”
mentioning
confidence: 95%
“…Psychologists have long regarded hallucinations as indicators of serious psychological disturbance (e.g. Esquirol, 1832;Heilbrun, 1980;Jaspers, 1911;Schneider, 1959). However, humankind has been familiar with hallucinatory experiences for even longer, at least since biblical times (Preuss, 1975).…”
mentioning
confidence: 99%
“…Heilbrun found that 12 psychiatric patients with a history of hallucinations turned out to be insuffi ciently capable of identifying the words, meaning, and grammatical style of their own spoken sentences following a 1-week lapse of time, as compared to eight nonhallucinating psychiatric patients. Incidentally, the two groups did not differ with regard to their ability to remember verbal material, the stability of their opinions, or the level of their communication skills (Heilbrun 1980 ) . A meta-analysis of 23 studies carried out over the past 30 years confi rmed that individuals diagnosed with schizophrenia who are prone to hallucinations tend to attribute self-generated thoughts and utterances to other people (Waters and Badcock 2010 ) .…”
Section: Source Monitoringmentioning
confidence: 80%